SUNNATULLAH DALAM PANDANGAN HARUN NASUTION DAN NURCHOLISH MADJID - Arbiyah Lubis (Islam Futura, 2012)
Difference view in comprehending Sunnatullah stemming from differences of theology confidence are held. Harun and Nurchalis, although both confessed as Islam rationalist, but they not agree in comprehending the nature of remain and not change at Sunatullah. Confidence at absolute or the limited power of God seems to be the root of their difference view in this case, such as those happened in classic Islam theologians are divided in firqah-firqah with the theories that they carry and up to now still live and expand